Reforming tax systems in the developing world: What can we learn from the past? - Roel Dom; Mark Miller (Overseas Development Institute (ODI), 2018)
There are questions to be asked about the wisdom of spending more aid on tax. Is it simply the case that the nature of current support and the way in which it is delivered is adequate, but that there is just not enough of it? If so, all that is needed is more of the same. Or, do we also need to rethink both the content and approach to international tax advice? One way of supporting more critical deliberation over the nature of technical cooperation is to better understand how ideas have evolved as well as the lessons that have been learnt (and not learnt) from past efforts to strengthen tax systems. This paper adds to the discussion by providing an accessible summary of the key academic ideas and policy debates over the past century that have shaped the nature of technical cooperation on tax system reforms in developing countries. It then connects these debates with the direction of travel of international cooperation on taxation.
Keywords: 330